THE INFLUENCE OF AEROBIC EXERCISE ON FATIGUE, ACTIVITIES OF DAILY LIVING AND AEROBIC FITNESS IN POST GASTRECTOMY INDIVIDUALS UNDERGOING CHEMOTHERAPY (International Journal of Physiotherapy, 2015)
Background: Gastric cancer is the second most common cancer among men and third most among women in world wide. For over 100 years, gastric cancer has remained one of the most important malignant diseases with significant, geographical, ethnic and socio-economic differences in distribution. The main aim of the study is to evaluate the effectiveness of supervised aerobic exercises on severity of fatigue, activities of daily living and aerobic fitness in post gastrectomy individuals undergoing chemotherapy.Methods: Total sixty patient’s age 30 to 68 years post gastrectomy individuals undergoing chemotherapy included for study. These patients were randomly allocated to intervention group (n=30), which underwent a 4- weeks training programme of supervised aerobic exercises & control group (n=30) that received standard care and unsupervised aerobic exercise protocol. Primary outcome was change in fatigue levels as determined by fatigue severity scale in before and after the intervention program. Secondary outcomes were activities of daily living and aerobic fitness as assessed by the dukes activity status index and six minute walk test by using cahalin formula. Paired sample t- test was used to analyse changes from before and after intervention programme.Result: There is a statistically significant (p